BAHASA BALI DALAM INTERAKSI DIGITAL: STUDI LANSKAP LINGUISTIK VIRTUAL PADA AKUN X @TimpalBali - Maharani, Ida Ayu (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This study employs the Virtual Linguistic Landscape (VLL) approach to explore the use of Balinese language in a multilingual digital space, particularly within the interactions on the social media account @TimpalBali. This descriptive qualitative research aims to understand the dynamics of Balinese language use alongside the dominance of the Indonesian language in digital content. The main focus of the study is on the analysis of top-down content, created by the account managers, and bottom-up content, generated through user interactions. The analysis involves identifying language dominance and uncovering the informational and symbolic functions of the Balinese language in both types of content. The findings reveal that top-down content tends to use Indonesian for informational purposes, such as delivering general information or reaching a wider audience. However, Balinese still appears as a symbolic element, highlighting cultural identity and supporting the preservation of the local language. In contrast, in bottom-up content, the Balinese language is more dominantly used by the user community. This use not only serves informational purposes as a communication tool but also carries a greater symbolic value. Balinese is used to create solidarity and closeness among community members while also marking a strong cultural identity. Furthermore, the use of Balinese in semi-formal user-generated content shows the influence of the language strategies implemented in the top-down content by the account managers. This study emphasizes the importance of social media, like the @TimpalBali account, as a digital space that supports the preservation of Balinese language and strengthens cultural identity. Thus, the account not only serves as an informational platform but also as a medium for preserving cultural heritage in the digital age.